2022
DOI: 10.21123/bsj.2022.19.4.0821
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes Prediction of Homeostasis Model Assessment of Beta-cells Function (HOMA-B) and C-peptide Level during Pregnancy: New Insight into Beta-cells Proliferation and Insulin Sensitivity

Abstract: This work aims to detect the associations of C-peptide and the homeostasis model assessment of beta-cells function (HOMA2-B%) with inflammatory biomarkers in pregnant-women in comparison with non-pregnant women. Sera of 28 normal pregnant women at late pregnancy versus 27 matched age nonpregnant women (control), were used to estimate C-peptide, triiodothyronine (T3), and thyroxin (T4) by Enzyme-linked-immunosorbent assay (ELISA), fasting blood sugar (FBS) by automatic analyzer Biolis 24i, hematology-tests by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous studies reported that chronic excessive fluoride intake is associated with several pregnancy complications 18,19 . On the other hand, it was reported that pregnancy showed behavioral, anatomical, physiological, and metabolic changes leading to dramatic variations in the concentration of several biochemical constituents of blood such as the antioxidant system, and certain minerals, mainly calcium 1,2,20 . These normal physiological changes are important for normal embryonic, placental, and fetal development 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that chronic excessive fluoride intake is associated with several pregnancy complications 18,19 . On the other hand, it was reported that pregnancy showed behavioral, anatomical, physiological, and metabolic changes leading to dramatic variations in the concentration of several biochemical constituents of blood such as the antioxidant system, and certain minerals, mainly calcium 1,2,20 . These normal physiological changes are important for normal embryonic, placental, and fetal development 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Pregnancy is a physiological period of transition with important physical and hormonal changes 1 . During pregnancy, significant anatomical and physiological changes occur in order to support and accommodate the growing fetus 2 . These changes require increased production of ATP, which in turn requires high consumption of oxygen.…”
Section: Introductionmentioning
confidence: 99%